2021
DOI: 10.3390/coatings11050576
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Electroless Nickel–Boron Deposit from Optimized Stabilizer-Free Bath

Abstract: Conventional electroless nickel–boron deposits are produced using solutions that contain lead or thallium, which must be eliminated due to their toxicity. In this research, electroless nickel–boron deposits were produced in a stabilizer-free bath that does not include any toxic heavy metal. During processing, the plating rate increased from 10 to 14.5 µm/h by decreasing the concentration of the reducing agent, leading to increased bath stability. The thickness, composition, roughness, morphology, hardness, wea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 35 publications
4
28
0
Order By: Relevance
“…The substrate is a catalytic surface on which metal is to be deposited. This reaction can be divided into two sections according to mixed potential theory [42,73]: cathodic partial reactions and anodic partial reactions. Cathodic partial reaction (Equation (2)) and anodic partial reaction (Equation (3)) are used to reduce metal ions and oxidize the reducing agent.…”
Section: Electroless Deposition Of Coppermentioning
confidence: 99%
See 2 more Smart Citations
“…The substrate is a catalytic surface on which metal is to be deposited. This reaction can be divided into two sections according to mixed potential theory [42,73]: cathodic partial reactions and anodic partial reactions. Cathodic partial reaction (Equation (2)) and anodic partial reaction (Equation (3)) are used to reduce metal ions and oxidize the reducing agent.…”
Section: Electroless Deposition Of Coppermentioning
confidence: 99%
“…An electroless deposition bath consists of metal ion sources, reducing agents, complexing agents, and additives. Reducing agents are the solution's driving force for reducing metal ions [64][65][66][67][68][69][70][71][72][73][74]. Electroless deposition is initiated once catalyst particles are available on the substrate surface [67].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers found that the deposition rate increased and decreased with increasing concentrations of nickel sulfate, sodium hypophosphite, pH, and bath temperature 23–25 . However, Yunacti et al 26 . found that during processing, the plating rate increased with decreasing reducing agent concentration.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers found that the deposition rate increased and decreased with increasing concentrations of nickel sulfate, sodium hypophosphite, pH, and bath temperature. [23][24][25] However, Yunacti et al 26 found that during processing, the plating rate increased with decreasing reducing agent concentration. To understand the intrinsic relationship between the deposition rate during process and the duration, researches [27][28][29] showed that electroless plating consists of different stages with various deposition rates.…”
Section: Introductionmentioning
confidence: 99%